LEX.CH.IT: A CORPUS FOR MICRO-DIACHRONIC LINGUISTIC INVESTIGATIONS OF SWISS NORMATIVE ACTS IN ITALIAN - CANAVESE, Paolo (Comparative Legilinguistics, 2019)
The aim of this paper is to present LEX.CH.IT, a corpus for micro-diachronic linguistic investigations of Swiss normative acts in Italian. Italian has a peculiar position as an official minority translation language within the Swiss institutional system. Until now, few studies have focused on Swiss legal Italian, but the academic interest has been growing over the last two decades. In order to further expand on research in this field, resources such as corpora are fundamental. This is why LEX.CH.IT has been compiled. This corpus was originally created in the context of a doctoral research project, which will be briefly outlined in this paper. The main goals of the project are to determine whether clarity is a feature of Swiss legislation in Italian, whether there have been relevant evolutions over the last five decades and to assess the role of translation for a clear legislation. In the future, LEX.CH.IT could also be useful for a number of other projects aiming to shed light on the features of this language variety.